Les aqueducs de Lyon à l’approche de la ville antique - Emmanuelle Dumas (Gallia)
The research conducted on the aqueducts of Lugdunum over the last thirty years, as urban development has continued over the Lyon metropolitan area, has helped us learn a little more about their approach route to the ancient city.The Gier aqueduct has now been found in thirteen places on the Sainte-Foy plateau, where it passed underground and above ground. It arrived there at an altitude of 305.80 m and left at an altitude of 301.60 m. The terminal reservoir of the siphon which enabled it to reach this plateau was revealed during excavations and a new study of the piers of the siphon bridge has taught us a little more about their method of construction near the Yzeron watercourse. Its underground canal was spotted in five places on the plateau and its aerial sections (the three rows of arches and the retaining walls) in six places. The aqueduct then had to cross the Col de Trion along an initially rectilinear route. It arrived on the hill at an altitude of around 300 m and entered the city: a line of arches, vestiges of which are preserved on rue Roger-Radisson. It still remains the only aqueduct for which remains have been found on both sides of the Col de Trion.The Brévenne aqueduct was observed in six places on the Point-du-Jour plateau. It arrived at an altitude of over 282.34 m and crossed most of the plateau on a line of arches. However, because of the significant levelling of its remains, we cannot estimate the altitude of the aqueduct channel in this sector. The siphon’s arrival point may be located around ten metres further downstream than had previously been envisaged, based on a rereading of the remains found at its western end. At its eastern end, little can be discovered. It is possible that its line of arches was interrupted and that the canal went underground if the recovery trench and the underground canal which were discovered there were in fact connected to it. Beyond the plateau, no more remains have been found. It must have crossed the Col de Trion by means of a siphon, whose route was probably quite close to that of the Gier or slightly more to the east, arriving on Fourvière Hill at an altitude of around 283 m.The Mont d’Or aqueduct is now known from five discovery points on the Point-du-Jour plateau where it fell from an altitude of 265 to 261 m. It reached there via a siphon whose leak tank may have been identified in a meadow located on the edges of the Sauvegarde plateau. Its route could have been more to the west than previously envisaged if the masonry heaps discovered at the north-west end of the Point-du-Jour plateau belong to it. Its penstock could have been formed from the only terracotta pipe unearthed on the Sauvegarde plateau. The trench in which this pipe would have been located was successfully followed for 800 m towards the siphon bridge, piers of which were discovered in the valley formed by the Planches and Chalin streams. The last known point of this aqueduct is located at the entrance to the Col de Trion, which it had to cross in a free buried pipeline following the contour lines to reach the urban districts of the eastern slope of Fourvière Hill at an altitude of slightly less than 261 m.For its part, the Yzeron aqueduct has been spotted in only two places on the Point-du-Jour plateau, which it crossed via an underground pipeline. It reached there via a siphon at an altitude of over 271.80 m. The rediscovery of one of the piers of its siphon bridge during excavations added to our knowledge of their construction method. It then had to cross the Col de Trion in a free overhead pipeline, 2 to 4 m high, before running underground to the urban districts of the eastern slope of Fourvière at around 268 m.The Gier aqueduct thus still remains the only one of the four whose remains have been found beyond the Point-du-Jour plateau as well as the only one whose arrival point on Fourvière Hill is known. On approaching the city of Lyon, these aqueducts ran alongside burial grounds, suburban housing and small workshops. Their immediate environment, which until recently was largely unknown, is only just beginning to be understood thanks to two excavations.